Illocutionary Acts and Public Reactions to Donald Trump’s 2024 Presidential Campaign Tweets - Nauli Rachma Fauzi Simanjuntak; Yessa Audry Suseno; Yanti Rosalinah (RETORIKA: Jurnal Ilmu Bahasa, 2025)
This study examines the use of illocutionary acts in the public’s reactions to Donald Trump’s tweets on X (formerly Twitter) during his 2024 presidential campaign, guided by Searle's felicity theory. We analyse posts from the official Donald J. Trump account on X from September 1-30, 2024, using qualitative methods in digital setting, with the researcher as the primary instrument. The study is descriptive and inductive, focusing on the content and meaning of illocutionary acts and public reactions, rather than numerical data or predefined hypotheses. Our aim is to understand how these acts influence public reactions, which we categorize as negative or positive, to reveal the link between Trump’s tweets and their role in political discourse. The results show that the directive act dominate Trump’s tweets, reflecting his intent to influence behaviour. Meanwhile some of the tweets meet Searle’s felicity conditions, others do not, resulting polarized public reactions. Trump’s communication appears partially effective, reinforcing support within his base while provoking backlash from critics, highlighting how illocutionary force in social media can shape political strategies and deepen public divides